Magnetic nanomaterials for hyperthermia-based therapy and controlled drug delivery - Yu Chen; Haifu Sun; Yonggang Li; Xixi Han; Yuqing Yang; Zheng Chen; Xuequan Zhao; Yuchen Qian; Xishui Liu; Feng Zhou; Jiaxiang Bai; Yusen Qiao (Bioactive Materials, 2025)
As an innovative physiotherapeutic approach, magnetic hyperthermia therapy (MHT) has unique advantages including minimal invasiveness, precise temperature control, and deep tissue penetration capabilities. It offers unparalleled control over heating areas and temperatures, boasts high efficiency, and results in excellent tissue penetration, while remaining independent of biological tissues. With vast potential in biomedical applications ranging from antitumor therapy to thrombus dissolution, MHT harnesses magnetic nanoparticles (MNPs) to convert magnetic energy into thermal energy under an alternating magnetic field (AMF), thereby achieving therapeutic effects. Advanced magnetic nanocomposite platforms based on magnetic nanoparticles can avoid various risks associated with traditional tools, achieving precise, on-demand, or continuous targeted drug delivery and release through multiple approaches. The potential clinical applications of magnetic hyperthermia therapy are being progressively developed. The present article presents an exhaustive review of the research progress in magnetic hyperthermia therapy. Initially, the overall landscape of MHT was outlined, including physical heat generation mechanisms, types of magnetic nanoparticles and conductive nonmagnetic materials, strategies to increase the thermal efficiency of MNPs, and experimental evidence and research progress on “hot-spot” effects. This review has focused on biomedical applications and targeted drug delivery of innovative combination therapy strategies based on MHT. The progress of clinical trials on MNPs-mediated MHT (MNPs-MHT) is summarized below. Furthermore, the limitations, major challenges and prospects in the clinical translation of MHT are discussed. The objective of this work is to provide a panoramic view of biomedical applications and targeted drug delivery of MHT, which can potentially guide researchers and facilitate the successful implementation of advanced MNPs-MHT systems in the future.